Teletherapy as an Alternate Model for Therapeutic Interventions for Children with Neurodevelopmental Disabilities in a Low-resource Setting in Jharkhand, India - Shabnam Rangwala (Indian Journal of Physical Medicine & Rehabilitation)
Background: This project was a collaboration between a community-based organization in rural India and a professional organization providing training and teletherapy support. The objective was to address the human resource gaps in rural areas for delivering therapeutic interventions to children with neurodevelopmental disabilities (NDD) in low-resource settings. Objective: To empower health workers in rural areas with the skills necessary to provide need-based therapeutic interventi ons to children with developmental disabilities through training and teletherapy. Methods: The project began with an initial training phase consisting of 10 online training sessions. This was followed by five additional need-based online training sessions over a 9-month period. Thirty-one children with NDD (15 girls and 16 boys) were enrolled and tracked using the Canadian Occupational Performance Measure (COPM). A total of 750 need-based therapy interventions, including physiotherapy, occupational therapy, and speech therapy, were provided by professional therapists via teletherapy. Results: The children showed significant improvement in the functional goals set from baseline to midline and end line. A one-way repeated-measures ANOVA test revealed a significant positive impact of teletherapy on the functional goals planned for the sample (P < 0.5). Conclusion: Teletherapy demonstrated a positive impact on achieving functional goals for children with NDD in rural Jharkhand. It is recommended as an effective model to address human resource gaps and provide family-centered therapeutic support in low-resource rural areas.